Pemberdayaan Ibu-Ibu Pengajian KKSS Sowi Gunung Melalui Pelatihan Manajemen Keuangan Usaha Mikro Berbasis Digital - Wahyuni, Sri; Lucia Klemensia Rahaded; Febianus Heatubun (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the financial literacy and digital capabilities of women in the KKSS Sowi Gunung religious group in Manokwari through Digital-Based Micro Business Financial Management Training. The activity was conducted on Sunday, September 28, 2025, from 4:30 p.m. to 6:30 p.m. WIT at Musholah Al-Haramain FSD Sowi Manokwari, and attended by 30 participants. The training was designed as a form of women’s empowerment to encourage independent, transparent, and modern financial management among micro-entrepreneurs. The implementation methods included interactive lectures, hands-on simulations using digital financial applications, and small group discussions to share real experiences and business challenges. The results showed a significant improvement in participants’ understanding of financial recording and practical skills in using mobile-based financial applications. Before the training, most participants did not record their financial transactions systematically; however, after the activity, 26 out of 30 participants successfully created simple financial statements separating capital, income, and expenses. The training also strengthened social cohesion and collaborative spirit among members of the religious group in developing their home-based businesses. Participants expressed greater confidence in maintaining consistent digital recording practices and agreed to continue learning through an online discussion group formed after the training.This activity demonstrates that digital transformation can begin with small and practical steps within women’s community groups. Through an educational and participatory approach, the training successfully fostered awareness that effective financial management is a key foundation for sustaining and growing micro-enterprises in the digital era.